PELANGGARAN PRINSIP KESANTUNAN BERBAHASA DALAM KOMUNIKASI MELALUI PESAN WHATSAPP ANTARA MAHASISWA DAN DOSEN - Amalia Fajriyyatin Najichah; Kurnia Dewi Nurfadilah (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2021)
This research aimed at describing the differences in the distribution of maxim violations of politeness principles in the communication through WhatsApp messages between students and lecturers from five higher education institutions in Indonesia. The method applied in this study was descriptive-qualitative with a pragmatic approach. The sources of the data were WhatsApp messages sent and received between students and lecturers at UIN Walisongo, IAIN Syekh Nurjati, IAIN Bengkulu, Universitas Cenderawasih, and Universitas Singaperbangsa.  The result of this study showed that there were four politeness principles violated by the students and the lecturers in their communications via WhatsApp. The highest violations were found at UIN Walisongo with four types of maxim violations. The second place were taken by Universitas Singaperbangsa with three types and the lowest ones occurred at IAIN Syech Nurjati, IAIN Bengkulu, and Universitas Cenderawasih, each with only two types of maxim violations.